POWER AND TERRITORY. CRISIS AND ECCLESIASTICAL DISPUTES BETWEEN SAN SALVADOR AND GUATEMALA, 1822-1842 - González Torres, Julián (2021)
This research is an approach to the diocesan institution as iurisdictio, whose roots go back to the times of the Roman colonization in the Iberian Peninsula. This in order to review the importance that the struggle for the erection of a diocese within its territory had for the State of Salvador, after the independence of the Central American provinces. The core of the study is based on the analysis of primary sources reviewed and digitally found in the Archdiocesan Historical Archive of Guatemala, mainly correspondence between the political and ecclesiastical authorities of San Salvador and those of Guatemala. From the review of these sources and the analysis of contemporary authors who work on issues related to the Catholic Church, from the colonial period to the Republican era, it is concluded that the authorities of San Salvador believed that as long as the state did not have a diocese in its territory political emancipation would be incomplete. In this way, I would like to offer another perspective of analysis in order to make the study of Central American and Salvadoran political emancipation more complex.